The Socialization of Toontastic Animation 3D Application in Increasing Interest of Class V Students of State Primary School 040447 Kabanjahe - Juwita Tindaon; Elisabeth Ruthana Lasmaria Sinaga; Dina Elvionica Br Siregar; Rian Julfian Sinaga; Seri Nita Br Ginting Suka (Jurnal Pengabdian Masyarakat Bestari, 2023)
Training on developing multimedia learning media using the Kinemaster, YouTube and Toontastic programs aims to provide skills in creating multimedia learning media in the form of interesting videos in a relatively easy way. The methods used are the Presentation Method regarding the introduction of software, the Demonstration Method and the Practical Method. The evaluation method is by observing the differences in teacher abilities before and after training. From the results achieved, it can be seen that there has been a significant increase in abilities compared to before training, so it can be concluded that this activity was successful in improving the participants' abilities. At the end of the activity the implementer of the community service program will capture data on the program's meaningfulness to the participants. It is hoped that this training program will continue to be held because it is very beneficial for improving the quality of learning, especially in this era.